Serological Evidence of Herpes Simplex Virus-1 (HSV-1) Infection among Humans from Bandung, West Java Province, Indonesia - Hakim, Dzulfikar Djalil Lukmanul; Gurnida, Dida Akhmad; Nuraeny, Nanan; Susilaningsih, Fransisca Sri; Herawati, Dewi Marhaeni Diah (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Toxoplasma gondii, Rubella virus, Cytomegalovirus, and herpes simplex virus (TORCH) infection is still a significant burden in developing countries since they potentially increase perinatal death and decrease life quality by causing congenital disorders. As part of TORCH and as one of the most common infections in humans, HSV Type 1 infection also should receive attention. HSV-1 infection induces an immediate reactive oxygen species (ROS) production, indicate that ROS plays beneficial effects in several biological functions, including innate immunity and antiviral responses. HSV-1 preferentially replicate and establish latency in different subtypes of sensory neurons and in neurons of the autonomic nervous system that are highly responsive to stress hormones, including cortisol. AIM: The objective of the study was to detect the latent HSV-1 infection in adults population and its effect on ROS and cortisol levels. PATIENTS AND METHODS: Subjects were enrolled with consecutive-sampling methods among the adults population age 18–40 years old, with no health complaints. We collected their blood to examined IgG HSV-1, ROS, and cortisol levels. RESULTS: A total of 57 subjects with 27 subjects were reactive IgG HSV-1 (herpes group) and 30 subjects were non-reactive IgG HSV-1 (non herpes groups). Mean of cortisol and ROS was 223.2904 nmol/L and 2.23337 IU/mL, respectively. There was a very weak correlation between HSV-1 infection with ROS and cortisol. CONCLUSION: There is a positive effect of latent HSV-1 infection in the adult population on cortisol ROS levels.